"Prá soletrar a Liberdade ": as propostas educacionais do movimento Zapatista no México e dos Sem-terras no Brasil na década de 90 - Mendes, Clécio Ferreira (2005)
ABSTRACT The purpose of this study is to analyse the educational concepts of Landless Rural Workers Movement (MST), in Brazil, and of Zapatist Army of National Liberation, in Mexico. Our goal is to verify convergent and divergent aspects among their speeches which are the basis of their educational practices. We intend to analyse how the educational proposal of these movements express the revindications of the rural population which historically, struggle for the land. As to the Zapatist case, their historical revindications are based on the common appropriation of the land, being common also the decisions regarding production and distribution. In the case of MST, proposals aiming the organization of cooperatives and the communization of production and distribution are found even in the field of education. Both movements have educational projects which reflect ideologies defended by them and, in their struggles, they display the contradictions of capitalist system. Such contradictions become more intense due to the advancement of neoliberal policies and direct the fight of both movements against neoliberalism and its consequences. It is therefore necessary to understand neoliberalism in Latin America not only as an economic trend but also as a kind of dictatorship which marginalizes and restrain the social struggles and movements. This study intends to rescue educational projects, while expression of their historicity, that is, while ideological representation of people who are deprived of socially produced goods. One of the main reflections derived from these movements is related to the way social movements act, creating new paths which are followed by new social movements facing old dilemmas.